Avaliação e ensino de relações número-quantidade para crianças da educação infantil e do ensino fundamental - Vernini, Amanda Rossi (Universidade Federal de São Carlos, 2023)
In the second half of 2021, in-person classes were resumed, after more than a year of isolation due to the COVID-19 pandemic, with the importance of monitoring and developing teaching procedures to meet the needs of children. The present study had two objectives: (1) to evaluate the repertoire of relating and naming numbers and quantities of preschool children and children in elementary school and (2) to evaluate the effects of teaching the relationships between dictated numbers, numbers, and quantity, through a procedure based on the equivalence of stimuli, applied on paper. Participated in the evaluation of the repertoire, five children from kindergarten and four children from elementary school, enrolled in a public school in the interior of São Paulo. A pre- and post-test design and a multiple probe design between stimulus groups were used. The general procedure consisted of 10 steps, starting with the familiarization with the participant. Then, the assessment was applied with the Protocol for Registration and Assessment of Mathematics Skills (PRAHM) instrument. The next step was the naming pre-test to measure performance in naming numerals and their respective quantities (from 1 to 9). After, pre-training to prepare the child for the experimental procedure. All relations AB (dictated numeral and numeral), AC (dictated numeral and quantity), BC (numeral and quantity) and CB (quantity and numeral) were applied. Based on the results of the pre-test, four children mastered the evaluated repertoires and five children realized the teaching procedure, three from kindergarten and two from elementary school. The teaching and testing stages of Group 1 were conducted up to criterion and again the probes and so on with the other two groups. After the last probe, the PRAHM, the naming post-test, and the Family Environment Resources Inventory (RAF) were applied. The data showed that four children completed the teaching procedure and one child taught the first group of stimuli. In general, the results showed that teaching was efficient for learning numbers and quantities. In the final evaluation, it was verified that the children showed an increase in the naming of numbers and quantities and they also increased their performance in the PRAHM skills. Thus, it is concluded that teaching was effective and developed the mathematical skills expected for this age group.
Assessment and teaching of number-quantity relationships for preschool and elementary school children
Keywords: Habilidades matemáticas; Equivalência de estímulos; Educação matemática; Ensino presencial; Math Skills; Stimulus equivalence; Mathematics education; Face-to-face teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM